Recent Advances in Understanding the Relationship between the Human Gut Microbiome and Gastrointestinal Health - Jumaah, Ali Salah; Ahmed Hasan, Ali Almurtadha; Jasim, Forqan Sameer (American Journal of Biology and Natural Sciences, 2025)
One of the key factors influencing gastrointestinal and systemic health in humans is the gut microbiota. It is made up of trillions of microorganisms that interact dynamically with the physiology of their hosts, such as bacteria, viruses, fungus, and archaea. These microbes are not passive commensals; rather, they actively support immunological control, food metabolism, mucosal barrier integrity, and inter-organ communication through the gut–liver and gut–brain axis. There is mounting evidence that the microbial fermentation of dietary fibers produces short-chain fatty acids (SCFAs), which are essential for preserving intestinal homeostasis and preventing inflammation, metabolic disorders, and cancer. On the other hand, a variety of gastrointestinal disorders, such as inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), celiac disease, colorectal cancer, and extra-intestinal conditions like obesity, non-alcoholic fatty liver disease, and type 2 diabetes, have been linked to dysbiosis, or disruption of the gut microbial community. Recent research on the dynamics and makeup of the gut microbiota, its roles in gastrointestinal disorders, and its mechanisms of action in health are summarized in this overview. We also examine new therapeutic approaches, such as fecal microbiota transplantation (FMT), tailored probiotics, precision nutrition, and probiotics and prebiotics. Lastly, we highlight the potential of microbiome-based therapies in personalized medicine while talking about current issues and potential future research avenues.